The relationship of community leaders and social cultural environment with community participation in management of COVID-19 in Tangerang City - Thoyib, Mastur; Widodo, Widodo; Rohati, Rohati; Mulyadi, Edi; Sutarman, Sutarman (Linguistics and Culture Review, 2021)
This study is to obtain data related to the correlation of community leaders’ leadership and the socio-cultural environment (independent variable) with community participation in handling Covid 19 (dependent variable), both varcial (each independent variable) or together. The line of thought in this study uses a correlational quantitative approach. The sample involved 100 community members, which is 20% of the total 520 population in the RW. 06 Padurenan Village, Karang Tengah District, Tangerang City, and selected by proportional random sampling. Data was collected using a questionnaire that was calibrated before use. This study produces data: (1) that the leadership of community leaders has a positive and significant relationship with community participation in preventing Covid 19, with a value of ry.1 = 0.669 > rtable (rtable = 0.195 at = 0.05 and rtable = 0.256 at = 0 ,01). (2) that the socio-cultural environment has a positive and significant relationship with community participation in handling Covid 19, with a value of ry.1 = 0.697 > rtable (rtable = 0.195 at = 0.05 and rtable = 0.256 at = 0.01).